NATURAL COLORS IN INDIAN SOCIAL TRADITION: भारतीय सामाजिक परम्परा में प्राकृतिक रंग - Swami, Meenakshi (International Journal of Research -GRANTHAALAYAH, 2014)
Ramdhari Singh Dinkar states that “Indian social life is enriched by traditions. The colorful painting on pottery in the Indus civilization is a testimony to the importance of painting in our tradition. Figures colored in red and yellow symbolize Indian social traditions. The consciousness of the throbbing body within the society is an expression of impulses attested through colors. Painting with colors derived from nature occurred in prehistoric times. Such as black, red, white, yellow, blue etc. Folk art is based on emotions and traditions. It is an expression of the feelings of the common man. The color combination based on divine signs and traditional beliefs is expressed in social traditions. रामधारी सिंह दिनकर का कथन है “भारतीय सामाजिक जीवन परम्पराओं से सम्पृक्त है। सिंधु सभ्यता में बर्तनों पर हुई रंग-बिरंगी चित्रकारी हमारी परम्परा में चित्रकला के महत्व का प्रमाण है। लाल और पीले रंगों से रंगी आकृतियाँ भारतीय सामाजिक परम्पराओं का प्रतीक है। समाज के भीतर धड़कती सजृन की चेतना रंगों के माध्यम से अनुप्रमाणित उद्वेगों की अभिव्यक्ति है। प्रकृति से प्राप्त रंगों से चित्रांकन का प्रागेतिहासिक काल में हुए। जैसे काले, लाल, सफेद, पीले, नीले आदि। लोक कला का संबंध भावनाओं और परम्पराओं पर आधारित है। यह जन सामान्य की अनुभूतियों की अभिव्यक्ति है। देवीय संकेतो व परम्परागत विष्वासों पर आधारित रंग संयोजन सामाजिक परम्पराओं में अभिव्यक्त होता है।